Mechanisms of Low‐Frequency Oxygen Variability in the North Pacific. Issue 2 (1st February 2019) - Ito, Takamitsu; Long, Matthew C.; Deutsch, Curtis; Minobe, Shoshiro; Sun, Daoxun
Abstract : This study investigates the mechanisms of interannual and decadal variability of dissolved oxygen (O2 ) in the North Pacific using historical observations and a hindcast simulation using the Community Earth System Model. The simulated variability of upper ocean (200 m) O2 is moderately correlated with observations where sampling density is relatively high. The dominant mode of O2 variability explains 24.8% of the variance and is significantly correlated with the Pacific Decadal Oscillation (PDO) index ( r = 0.68). Two primary mechanisms are hypothesized by which the PDO controls upper ocean O2 variability. Vertical movement of isopycnals ("heave") drives O2 variations in the deep tropics; isopycnal surfaces are depressed in the eastern tropics under the positive (El Niño‐like) phase of PDO, leading to O2 increases in the upper water column. In contrast to the tropics, changes in subduction are the primary control on extratropical O2 variability. These hypotheses are tested by contrasting O2 anomalies with the heave‐induced component of variability calculated from potential density anomalies. Isopycnal heave is the leading control on O2 variability in the tropics, but heave alone cannot fully explain the amplitude of tropical O2 variability, likely indicating reinforcing changes from the biological O2 consumption. Midlatitude O2 variability indeed reflects ocean ventilation downstream of the subduction region where O2 anomalies are correlated with the depth of winter mixed layer. These mechanisms, synchronized with the PDO, yield a basin‐scale pattern of O2 variability that are comparable in magnitude to the projected rates of ocean deoxygenation in this century under "unchecked" emission scenario. Plain Language Summary: In the North Pacific, oxygen levels in the seawater show large‐scale patterns associated with the regional climate on the timescales of years to decades. We used a computational model of circulation and cycling of elements in the ocean to simulate these changes for the last approximately 70 years. Our aim is to better understand what causes these changes. First, the climate shifts can move large volume of seawater up and down in the ocean and redistribute dissolved oxygen due to the large‐scale water movement. Second, the climate shifts can alter the rate at which oxygen‐rich surface waters can mix into the subsurface ocean. We found that both mechanisms are important, but they occur in different regions; the first mechanism is particularly important in the tropics, and the second mechanism dominates in the subtropics. We further found that the climate‐driven changes in the biological processes tend to reinforce the physically driven oxygen changes of the tropics. These insights can help better understand and interpret existing and future observations of oxygen changes. Key Points: Two hypotheses are proposed for upper ocean oxygen variability that is synchronized with the Pacific Decadal Oscillation Tropical variability is primarily controlled by the heave of isopycnal surfaces, while the subtropics are controlled by the ventilation Historic observations and a numerical model suggest additional, amplifying mechanisms that enhance tropical oxygen variability